Molecular Simulation Analyses of Polymorphism Control Factors by the Example of Carbamazepine Forms I-IV: A Blueprint for Industrial Drug Formulation? - Gadelmeier, Andreas; Macht, Moritz; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2022)
We outline comparably simple molecular simulation techniques to elucidate the interactions that determine the polymorphism of carbamazepine. Starting from the established GAFF molecular mechanics model, only a small series of tailor-made improvements is needed to tackle the subtle differences in the interaction energies of polymorphs I - IV. On this basis, molecular dynamics simulations provide melting enthalpies at < 1 kcal/mol accuracy (0.2 kcal/mol for forms I-III) as compared to the experiment. Yet, the predicted stability ranking of III > I > II > IV only partially reproduces the experimentally observed III > I > IV > II series. Despite this limitation, we demonstrate how insights from molecular simulation offer the elucidation of possible factors for polymorph control. Apart from characterizing bulk crystals, we outline the evaluation of size-dependent profiles of crystallite formation energy. Contrasting the contributions of bulk, surface and edge terms to the formation energy of nano-scale precipitates, we suggest a multi-step nucleation mechanism leading from amorphous aggregates to crystallites. We argue that carbamazepine aggregates of less than ∼100 molecules adopt a spherical shape to minimize edge/surface energy – overcompensating the loss in bulk energy inherent to non-crystalline ordering in the inner core. In turn, for large crystallites polymorph form III is preferred, whilst suitable spatial confinement to crystallites of 100–500 carbamazepine molecules appears to promote form II.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Crystal engineering; Drug formulation; Molecular simulation; Polymorphism